Representation of Motherhood in Film Ngeri-Ngeri Sedap: A Roland Barthes Semiotic Analysis - Siti Fadilla; Wahyudi Wahyudi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study analyzes the representation of motherhood in the Indonesian film Ngeri-Ngeri Sedap (2022), directed by Bene Dion Rajagukguk, using Roland Barthes’ semiotic approach. The research focuses on how denotative, connotative, and mythological meanings construct the social position of mothers within the patriarchal Batak family structure. A qualitative descriptive method was applied, with data sources consisting of 20 selected scenes featuring Mak Domu (portrayed by Tika Panggabean) as the central character. Barthes’ three-level semiotic analysis was applied to identify sign systems across denotation (literal meaning), connotation (cultural and emotional meaning), and myth (second-order signification). Findings reveal that the film constructs Mak Domu through two dominant patterns. First, the film reproduces patriarchal myths of the Batak mother as guardian of family unity, bearer of emotional burdens, and sacrificial figure who sustains domestic stability. Second, the film also negotiates these myths by representing Mak Domu as a moral agent who possesses bargaining power within the domestic sphere. The study concludes that the representation of motherhood simultaneously reflects and contests patriarchal Batak culture, functioning as a space of ideological negotiation between tradition and change in contemporary Indonesian cinema.